Identity: In Searching the Meaning of Chineseness in Greater China - Gordon C. K. Cheung (Copenhagen Business School (CBS), Asia Research Centre (ARC), 2006)
Among the people in Greater China (People's Republic of China [PRC], Taiwan and Hong Kong), needless to say, economic incentive, political relations and business relations all conjure up an ethos of relations, if not close bonds, among Hong Kong, Taiwan and the PRC. The rise of China matters to everyone who lives in Greater China. Hong Kong is already part of China. Taiwan, according to the PRC, cannot be independent without running the risk of a war. Yet, my question is that are those Chinese the same in Greater China? Do they have different identities? If living with China is inevitable, do they need to search for a new identity to face the challenges? Keywords: Chineseness, Greater China, identity, national boundaries, Hong Kong, Taiwan
hdl:10398/7396
Keywords: 330